2021
DOI: 10.1002/jmor.21392
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of a tiny gymnophalloid miracidium (Digenea)

Abstract: We elucidate the morphology of the miracidia with passive strategy of infection. In contrast to the well‐studied “active” free‐swimming larvae (e.g., those of Schistosoma, Fasciola, Echinostoma), “passive” miracidia do not search for their hosts in the external environment. The infection occurs only after the mollusk ingests the eggs with the larvae. The miracidia of this type are extremely miniaturized organisms whose somatic elements are reduced compared to the “active” forms. The details of the structure ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…contains a very small mother sporocyst, composed of just one tegument cell and two germ cells. This corresponds well with the reductive trends in all other miracidia following the passive strategy of infection (Galaktionov, Dobrovolskij, 2003;Świderski et al, 2010Smirnov, Dobrovolskij, 2019, 2021Smirnov, Gonchar, 2022), but Notocotylidae went the furthest. What prompted their larvae to achieve such an extreme level of simpli cation?…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…contains a very small mother sporocyst, composed of just one tegument cell and two germ cells. This corresponds well with the reductive trends in all other miracidia following the passive strategy of infection (Galaktionov, Dobrovolskij, 2003;Świderski et al, 2010Smirnov, Dobrovolskij, 2019, 2021Smirnov, Gonchar, 2022), but Notocotylidae went the furthest. What prompted their larvae to achieve such an extreme level of simpli cation?…”
Section: Discussionsupporting
confidence: 78%
“…We previously studied the ultrastructure of several passive miracidia (Smirnov, Dobrovolskij, 2019, 2021Smirnov, Gonchar, 2022) and found that they are highly miniaturized creatures that tend to lose most somatic elements typical for active larvae, but retain and differentiate penetration apparata. Apparently, this is a result of mastering the passive strategy of infection which drastically reduces the signi cance of some functions (e.g., sensory, locomotory, osmoregulatory), but creates some new issues associated with the in-gut activity (Smirnov, Gonchar, 2022).…”
Section: Introductionmentioning
confidence: 99%